Evaluation of coffee pulp as a feed ingredient for ruminants: A meta-analysis - Fhonna Fenda Alvionita; Jayanegara Anuraga; Sulaiman Ismail; Rahmadani Mardiah; Samadi Samadi (Open Agriculture)
This meta-analysis aimed to evaluate the potential of coffee pulp as ruminant feed. The database was developed from 22 related articles containing 94 studies, collected from Scopus and Google Scholar. The parameters integrated were ruminant intake, digestibility, ruminant performance, milk production, milk composition, carcass production, and rumen fermentation. The data were analyzed using a mixed model methodology. The level of coffee pulp was considered as a fixed factor and the different studies as random effects. The results revealed that coffee pulp addition had a significant quadratic effect on reducing the intake of dry matter, crude protein, and total digestible nutrients (P < 0.01), and had a linear response to enhance neutral detergent fiber and acid detergent fiber intake (P < 0.05). However, it should be noted that there were no significant differences in performance, nutrient digestibility, milk production and composition, carcass production, and rumen fermentation. by using coffee pulp as ruminant feed. In conclusion, coffee pulp can be used as an alternative feed ingredient for ruminants. However, it should be applied at the right amount to avoid negative effects on animal performance.